A phenomenological probe on the effects of parental involvement on learner achievement: base-reference for a benchmark for parent involvement programs - Lopez, Flordeliza A. (Parañaque City: Olivarez College, 2013)
This phenomenological research sought to extract meanings form the experiences of parents based on the central question, "In what ways does parental involvement at San Antonio Elementary School affect their children's academic achievement?" Accordingly, I examined what the pupils have in common when it comes to the role their parents play in their education, irrespective of their social-economic status and gender. The corollary questions were as follows: You sent Are the parents actively involved with their education? What is their attitude towards their child's education and education in general? Do they make any demands on their children with regards to their schooling? Do the parents have expectations of educational performances? Do they have expectations for their child's future college attendance? Do they convey these expectations to their children? Do the parents have relationships with other parents at school?
Master Thesis